A Literature Review of the Analytical Toxicology of Fentanyl Derivatives - Moriarty, Michaela; Heaney, Cathy; Kenny, Rachel; Moran, Julie; O'Malley, Ella (Trinity Student Medical Journal, 2025)
Introduction: Fentanyl is a synthetic opioid with the potential to cause life-threatening adverse effects in overdose scenarios, including sedation and respiratory depression. The rising prevalence of fentanyl-related substances since the mid-2000s constitutes a serious concern. Methods: This literature review offers a comprehensive overview of the current information available concerning fentanyl derivative toxicology, including testing methodologies in biological fluids, metabolism, pharmacokinetics and levels found in overdose or deaths associated with their use. Results: There are significant knowledge gaps in the current literature on fentanyl derivatives, partly due to their extremely low serum concentration. Lower limit of detection figures are typically in the range of 0-1 ng/mL, necessitating the use of highly sensitive testing methodologies. Immunoassays are widely available but limited in their ability to distinguish between derivatives. Gas chromatography-mass spectrometry offers untargeted data acquisition and vast mass spectral libraries; however, this technique has lengthy preparation times and limited sensitivity. Liquid chromatography-mass spectrometry has recently been used with quadrupole time-of-flight or orbitrap technology to offer tentative identification of compounds without library searching. However, the real weapon needed to tackle the ongoing fentanyl crisis is a technique which can assist in the prediction of unknown compounds. Discussion: The recent advent of a machine learning model applicable to mass spectra offers promising potential to predict the structure and spectra of previously unknown fentanyl analogues. Moreover, increased funding is required to enhance the sensitivity of current fentanyl detection techniques in combating the overdose epidemic.